2017
DOI: 10.1051/0004-6361/201732173
|View full text |Cite
|
Sign up to set email alerts
|

The Sunburst Arc: Direct Lyman α escape observed in the brightest known lensed galaxy

Abstract: We present rest-frame ultraviolet and optical spectroscopy of the brightest lensed galaxy yet discovered, at redshift z = 2.4. The source reveals a characteristic triple-peaked Lyman α profile that has been predicted in various theoretical works, but to our knowledge has not been unambiguously observed previously. The feature is well fit by a superposition of two components: a double-peak profile emerging from substantial radiative transfer, and a narrow, central component resulting from directly escaping Lyma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 31 publications
7
87
3
Order By: Relevance
“…The linear fits to the surface brightness profiles of the outer galaxy parts are shown by solid lines. and two z > 2 LyC leakers (Vanzella et al 2018;Rivera-Thorsen et al 2017). However, at variance with J1032+4919, all other triple-peaked spectra in the literature do not show clear signs of underlying Lyα absorption.…”
Section: Surface Brightness Distribution In the Nuv Rangementioning
confidence: 82%
“…The linear fits to the surface brightness profiles of the outer galaxy parts are shown by solid lines. and two z > 2 LyC leakers (Vanzella et al 2018;Rivera-Thorsen et al 2017). However, at variance with J1032+4919, all other triple-peaked spectra in the literature do not show clear signs of underlying Lyα absorption.…”
Section: Surface Brightness Distribution In the Nuv Rangementioning
confidence: 82%
“…The properties of low-ionization interstellar lines vary among the LyC emitters. While the absorption features such as Si IIλ1260, O Iλ1303 and C IIλ1334 are very weak or even absent in Ion2 Vanzella et al 2016) and Ion3 (Vanzella et al 2018), they are clearly observed in the Sunburst (Si IIλ1260, Rivera-Thorsen et al 2017 Shapley et al 2016), and Ion1 (see Figure 2). The scattering of the low-ionization absorption properties among the emitters suggests that the conditions under which ionizing radiation can escape from host galaxies are local, namely LyC photons can escape if there exists low neutral gas covering holes in the surrounding where the ionizing emission arise (the 1D spectrum of a galaxy is basically a luminosity-weighted average).…”
Section: Comparison Of Ion1 With Other Lyc Emitters At Intermediate Rmentioning
confidence: 99%
“…Because the assumption of the Reddy law with the STARBURST99 models yields an escape fraction as high as 93%, we conclude that the dust attenuation curve for the Sunburst Arc is indeed likely to be well approximated by the Reddy law. (13). Overlaid are theoretical and empirical stellar/AGN separation lines (49,55).…”
Section: Dust Attenuation Modelmentioning
confidence: 99%
“…S1). The Lyman-α profile indicated that it was a prime candidate for strong LyC escape through a narrow channel oriented towards Earth (13). Such a LyC channel should appear as a multiply-imaged, compact source coincident with some of the brightest regions seen in the extended, non-ionizing stellar continuum (19) when observed using telescopes with sufficient resolution and ultraviolet capabilities.…”
mentioning
confidence: 99%